Is There a Preinterventional Mechanical Ventilation Time Limit for Candidates of Adult Respiratory Extracorporeal Membrane Oxygenation. Issue 5 (September 2017) - Wu, Meng-Yu; Huang, Chung-Chi; Wu, Tzu-I; Chang, Yu-Sheng; Wang, Chin-Liang; Lin, Pyng-Jing
Abstract : Venovenous extracorporeal membrane oxygenation (VV-ECMO) is a useful life support in severe acute respiratory distress syndrome (ARDS). Although prolonged mechanical ventilation (MV) before institution of ECMO is known to be a poor prognostic factor for outcomes of VV-ECMO, a reasonable deadline for this period has not been defined yet. To discover the answer, we reviewed a 9 year institutional experience of adult respiratory ECMO in VV configuration and investigate the relationship between the MV time before ECMO and in-hospital mortality. This retrospective study included 129 adult patients receiving VV-ECMO for ARDS in a single institution from 2007 to 2016. Important demographic and clinical data before ECMO intervention were collected for analyses of in-hospital mortality. The MV time before ECMO independently predicted hospital death in adult respiratory ECMO here. While compared to the patients receiving MV for 7 days or less, the patients receiving MV for more than 7 days before ECMO showed a higher in-hospital mortality rate (77% vs. 38%, p < 0.001). They also experienced a more significant deterioration in respiratory function during MV before the institution of ECMO. Therefore, from the clinical observation, we thought that a 7 day period might be an acceptable limit on MV time before institution of VV-ECMO. Integrating other respiratory parameters into the current PaO2 /FiO2 (PF) ratio-based inclusion criteria of adult respiratory ECMO might be helpful to reduce the risk of prolonged MV in selected patients.